How do different diagnostic criteria, age and gender affect the prevalence of attention deficit hyperactivity disorder in adults? An epidemiological study in a Hungarian community sample - Bitter, István; Simon, Viktoria; Bálint, Sára; Mészáros, Ágnes; Czobor, Pál (European archives of psychiatry and clinical neuroscience, 2010)
The goal of the study was twofold: (1) to investigate the effect of different diagnostic criteria on prevalence estimates of adult attention deficit hyperactivity disorder (ADHD), and (2) to provide prevalence estimates of adult ADHD for the first time in a Hungarian sample. Subjects between 18 and 60 years were included in the screening phase of the study ( N = 3,529), conducted in 17 GP practices in Budapest. Adult self-report scale 6-item version was used for screening. Out of 279 positively screened subjects 161 subjects participated in a clinical interview and filled out a self-report questionnaire to confirm the diagnosis. Beside DSM-IV diagnostic criteria, we applied four alternative diagnostic criteria: ‘No-onset’ (DSM-IV criteria without the specific requirement for onset); full/Sx (DSM-IV “symptoms only” criteria); and reduced/Sx (DSM-IV “symptoms only” criteria with a reduced threshold for symptom count). Crude prevalence estimates adjusted for the specificity and sensitivity data of the screener were 1.35% in the ‘DSM-IV’ group, 1.64% in the ‘No-onset’ group, 3.65% in the ‘Sx/full’ group and 4.16% in the ‘Sx/reduced’ group. Logistic regression analysis showed that ADHD was significantly more prevalent with younger age and male gender [χ 2 = 14.46; P = 0.0007]. Prevalence estimates corrected for the ‘not-interviewed’ subsample and adjusted for specificity and sensitivity data of the screener was 2.3% in males, 0.91% in females; 2.02% in the ≤40 years age group and 0.70% in the >40 years age group, based on DSM-IV diagnostic criteria. Prevalence rates found in this study are somewhat lower, but still are in line with those reported in the literature.